Low-Loss Silicon Waveguides and Grating Couplers Fabricated Using Anisotropic Wet Etching Technique - Debnath, Kapil; Arimoto, Hideo; Husain, Muhammad K.; Prasmusinto, Alyssa; Al-Attili, Abdelrahman; Petra, Rafidah; Chong, Harold M. H.; Reed, Graham T.; Saito, Shinichi (Frontiers in Materials, 2016)
We report low-loss silicon waveguides and efficient grating coupler to couple light into them. By using anisotropic wet etching technique, we reduced the side wall roughness down to 1.2nm. The waveguides were patterned along the [112] direction on a [110] SOI substrate. The waveguide boundaries are decided by the [111] planes which are normal to the [110] surface. Fabricated waveguides show minimum propagation loss of 0.85 dB/cm for TE polarization and 1.08dB/cm for TM polarization. The fabricated grating couplers show coupling efficiency of -4.16dB at 1570nm with 3dB bandwidth of 46nm.